Pesticide contaminated crop residues and water usage for dairy cattle rearing in Walapane DS division, Sri Lanka - Pathirana, K.P.S.R.; Katukurunda, K.G.S.C.; Dilhani, R.A.D.I.; Marapana, R.A.U.J.; Jayasinghe, J.M.J.K.; Navaratne, S.B. (International Journal of Innovative Research in Technology, 2015)
Attached

Contamination of milk with pesticide residues is a matter of serious concern. The extensive use of pesticides may lead to environmental and food contamination also risk of contamination was occurred especially in up country because of scarcity of grazing lands. Abundance of crop residues in substantial amounts lead farmers to feed them adequately for cattle. Farmers who cultivate upcountry vegetables tend to apply higher amounts of pesticides due to the intensive cultivation of hybrid crop varieties and highly favorable weather conditions for the rapid spread of pests and diseases. The objectives of this study were to identify the types of pesticides used in the area, crop residues that are used as feed material and sources of contaminants which have an impact to the milk industry in Walapane. Primary data for the study were collected from thirty farmers randomly (n=30) representing three villages of Walapane DS division namely Ragala, Nildandahinna and Wewekelle. Major vegetables in the area were cabbage, tomato, beans, eggplant and carrot. Majority (64%) of milk farmers had Jersey crosses, while 36% had Friesian crosses. Most (53%) farmers carry out extensive rearing in roadsides and vegetable lands and intensive rearing of 47%. Farmers (84%) provide grasses and crop residues (16%) to cattle. Fresh grasses and crop residues were directly fed to cattle without any treatments. Farmers used well water (93%) and natural water stream (7%) as water sources. The majority (>90%) disposed the empty pesticide containers by throwing in the crop land and water sources itself. Farmers applied Mancozeb (47%), Propineb (37%), Fipronil (10%) and Maneb (6%) as pesticides for cultivation of vegetables nearby water sources while fungicides (Propineb 36% and Mancozeb 20%) applied nearby farm lands. Feeding with crop residues, grasses and water which were contaminated with pesticides encountered high risk to contain pesticide residues in milk in Walapane DS Division Sri Lanka
Keywords: Milk; Pesticides; Feed; Water; Walapane